A Prospective Multi-Centered Registry-Based Observational Study for Patients With Cancer: Design and Rationale for Korean Medicine Cancer Registry (KMCARE) - Jee Young Lee KMD, PhD; Hayun Jin KMD; Su Bin Park KMD, MS; Eun Hye Kim KMD, MS; Jee-Hyun Yoon KMD, PhD; Seong Woo Yoon KMD, PhD (Integrative Cancer Therapies, 2024)
Background: Cancer is one of the leading causes of death in most countries with an expected increased burden on healthcare systems. Since integrative medical treatments are not collected within the scope of existing cancer registries, the establishment of the Korean Medicine Cancer Registry (KMCARE), gathering integrative therapies, including conservative care and Korean medicine, is warranted. Methods: A prospective observational study based on the registry will be conducted in 5 Korean medical hospitals. A total of 650 eligible participants undergoing Korean medicine treatments within 1 month of a diagnosis of lung, colorectal, stomach, or breast cancer are anticipated to be enrolled in the registry. Data collected in the KMCARE can be classified into patient information, received treatments, and outcomes. The primary outcome is the Functional Assessment of Cancer Therapy-General Questionnaire score at 3 months. Secondary outcomes include the MD Anderson Symptom Inventory-Core and the Body Constitution Questionnaire at 3 and 6 months. After 6 months of follow-up periods, survival surveillance will be continued for additional 18 months. Descriptive and statistical analysis of primary and secondary outcomes, baseline data, safety, survival, and prognostic factors will be performed. Discussion: This is the first prospective, multi-centered, registry-based observational study of cancer patients in Korean medicine hospitals, which could reveal the current status of cancer patients receiving integrative cancer therapies, and provide better insight into the role of Korean medicine in palliative care for patients with cancer. Trial registration: Clinical Research Information Service (CRIS), KCT0007447.